Pengaruh Budaya Perusahaan, Pendidikan Pelatihan Dan Ethos Kerja Terhadap Motivasi Karyawan Serta Implikasinya Terhadap Kinerja Karyawan Pada Karyawan OPD BNI Syariah Pusat - Saputra, Ferdiansyah; Gustari, Irvandi; Sihite, Mombang (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2023)
This study aims to determine: (1) the influence of corporate culture on educational training for OPD BNI Syariah employees at the head office; (2) the effect of job training education on the work ethic of BNI Syariah OPD employees at the head office; (3) the effect of employee motivation on the performance of OPD BNI Syariah head office employees; (4) the influence of corporate culture on the work ethic of OPD BNI Syariah employees at the head office; (5) the influence of corporate culture on the motivation of OPD BNI Syariah head office employees; (6) the influence of corporate culture on the performance of OPD BNI Syariah head office employees; (7) the effect of job training education on the motivation and performance of OPD BNI Syariah head office employees. The results of this study are: (1) Organizational culture has a significant effect on motivation, t-value is 2.926 > t-table is 1.96 at a significance level of 5%. This means that organizational culture significantly affects motivation (2) Education and training have a positive and significant effect on motivation, t-value of 2.354 > t-table of 1.96 at a significance level of 5%. This means that education and training positively and significantly affect motivation. (3) work ethic has a positive and significant effect on motivation; t-value is 3.758 > t-table is 1.96 at a significance level of 5%. This means that work ethic has a positive and significant effect on motivation. (4) Organizational culture significantly affects performance, t-value of 2.354 > t-table of 1.96 at a significance level of 5%. This means that organizational culture has a significant effect on employee performance. (5) Education and training significantly affect performance, t-value of 3,390 > t-table of 1.96 at a significance level of 5%. This means that education and training have a significant effect on employee performance. (6) work ethic has no significant effect on employee performance; t-value is 1.789 < t-table is 1.96 at a significance level of 5%. This means that work ethic has no significant effect on employee performance (7) Motivation has a significant effect on employee performance, t-value of 2.163 > t-table of 1.96 at a significance level of 5%. This means that motivation has a significant effect on employee performance